2007
DOI: 10.1007/s10669-007-9047-2
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation of heavy metals by Eichhornia crassipes

Abstract: Eichhornia crassipes was tested for its ability to bioconcentrate 8 toxic metals (Ag, Cd, Cr, Cu, Hg, Ni, Pb, and Zn) commonly found in wastewater from industries. Young plants of equal size were grown hydroponically and amended with 0, 0.1, 0.3, 0.5, 1.0, 3.0, and 5.0 mM of each heavy metal individually for 21 days. The test plant had the lowest and the highest tolerance indices for Hg and Zn, respectively. A significant (P £ .05) reduction in biomass production was observed in metal treated plants compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(32 citation statements)
references
References 22 publications
2
30
0
Order By: Relevance
“…The main objective of this research was to evaluate the phytoremediation potential of C. roseus and study the effect of Cr stress on growth characteristics and alkaloid content of C. roseus. Recent studies have indicated that heavy metal stress increases the activity of antioxidant enzymes which play important roles in adaptation of plants to stress conditions [12]. Consequently, one of the aims of this study was also to examine whether Cr induced stress affects the antioxidant defense system, as well as the accumulation of alkaloids in C. roseus.…”
Section: Introductionmentioning
confidence: 99%
“…The main objective of this research was to evaluate the phytoremediation potential of C. roseus and study the effect of Cr stress on growth characteristics and alkaloid content of C. roseus. Recent studies have indicated that heavy metal stress increases the activity of antioxidant enzymes which play important roles in adaptation of plants to stress conditions [12]. Consequently, one of the aims of this study was also to examine whether Cr induced stress affects the antioxidant defense system, as well as the accumulation of alkaloids in C. roseus.…”
Section: Introductionmentioning
confidence: 99%
“…The phyotoxicity due to different elements depends on metal type, metal concentration and duration of exposure (ODJEGBA and FASIDI 2007). The metal uptake and distribution in submerged plant species vary according to the relative concentration of the elements in the environment, the growth of the plant, type of absorption mechanism, metal speciation, metal stability and constants with ligands, redox potential and pH at water-sediment interface, light, and microbial activity (NAGAJYOTI et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, other elements with lower concentrations than plants inhabiting other world rivers were Pb, Ni, Cu, and Zn. The tolerance of this species to several metals was analyzed under experimental conditions by Odjegba and Fasidi (2007), the authors detected that the order of tolerance was Zn>Cr>Ag>Pb>Cd>Cu>Ni>Hg. Thus, it is possible that the Zn and Cr concentrations of this study may not be considered detrimental to water hyacinth development.…”
Section: Discussionmentioning
confidence: 99%
“…An example is the hyperaccumulator Eichhornia crassipes (Mart.) Solms (water hyacinth), Pontederiaceae native to South America and widely distributed throughout the world (Odjegba and Fasidi, 2007). Depending on the river and the pollution source to the collecting point, Al, Cu, Fe, Mn, Ni, Cd, Cr, Co, Pb, Zn and Hg have previously been detected in water hyacinth plants (Vesk and Allaway, 1997;Klumpp et al, 2002;Soltan and Rashed, 2003;Mangabeira et al, 2004;Skinner et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation